2021
DOI: 10.1051/0004-6361/202039381
|View full text |Cite
|
Sign up to set email alerts
|

Kink instability of triangular jets in the solar atmosphere

Abstract: Context. It is known that hydrodynamic triangular jets (i.e. the jet with maximal velocity at its axis, which linearly decreases at both sides) are unstable to anti-symmetric kink perturbations. The inclusion of the magnetic field may lead to the stabilisation of the jets. Jets and complex magnetic fields are ubiquitous in the solar atmosphere, which suggests the possibility of the kink instability in certain cases. Aims. The aim of the paper is to study the kink instability of triangular jets sandwiched betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Kink instability is one of the prominent mechanisms to trigger the solar jets (see the review within Raouafi et al 2016). The observational and theoretical studies suggest that the rotational/twisting motions of the solar jets are directly linked with the helical kink instability (Shibata & Uchida 1986;Pariat et al 2009;Liu et al 2019;Zaqarashvili et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kink instability is one of the prominent mechanisms to trigger the solar jets (see the review within Raouafi et al 2016). The observational and theoretical studies suggest that the rotational/twisting motions of the solar jets are directly linked with the helical kink instability (Shibata & Uchida 1986;Pariat et al 2009;Liu et al 2019;Zaqarashvili et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other types of instabilities include the resonant flow instability (Tirry et al 1998;Taroyan & Erdélyi 2002) and shear flow instabilities (Taroyan & Ruderman 2011). Most recently, Zaqarashvili et al (2021) found that the dynamic kink instability of triangular jets can cause a complete breakdown of the MHD flows, which could result in the disappearance of spicules in solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the study of Barbulescu & Erdélyi (2018) can be considered a natural extension of this, as they focused on the effects of adding a steady background flow to the slab in an asymmetric slab system. A different type of extension is provided by Zaqarashvili et al (2021), who analyzed the stability of solar jets in slab geometries subject to a kink oscillation. This last example ties into another important line of investigation when it comes to generalizing slab models, especially the ones under the effect of background flows, namely, that of introducing nonuniformity in some parameters.…”
Section: Introductionmentioning
confidence: 99%